Bourbon and Rye Whiskeys Are Legally Distinct but Are Not Discriminated by Sensory Descriptive Analysis. Issue 3 (7th February 2019) - Lahne, Jacob; Abdi, Hervé; Collins, Thomas; Heymann, Hildegarde
Abstract : Abstract: We present a Descriptive Analysis (DA) of a large representative sample (24 whiskeys) of two legally distinct types of American whiskeys: bourbon and rye whiskey (respectively distilled from a fermented "mashbill" of at least 51% corn or rye). We wanted to determine whether a trained panel could find sensory differences between these two products. We used standard DA: 11 judges were trained for 10 hours to develop a lexicon of 24 flavor, taste, and mouthfeel descriptors for the 24 whiskey samples (15 bourbons and 9 ryes). Then, subjects rated each whiskey sample on each attribute, using unstructured line scales, in standard good sensory‐evaluation conditions, and in triplicate. Results were analyzed using MANOVA, Barycentric Discriminant Analysis, and Hierarchical Cluster Analysis. Overall, while 10 descriptors significantly differentiated the whiskeys, no attribute or combination of attributes was predicted by mashbill: The judges did not find differences in sensory character between bourbon and rye whiskeys as categories. However, significant differences could be attributed to the producer of the whiskey and to age at bottling. These results are important because American whiskey has recently become staggeringly popular, and because there is a consistent belief that bourbon and rye whiskeys—as categories—have distinct sensory characteristics. Practical Application: This research contradicts popular and expert beliefs about the distinction between the popular and important American rye and bourbon whiskeys. A comprehensive sensory DA study of 24 American whiskeys with different mashbills (9 ryes and 15 bourbons) shows that—while each whiskey is individually distinct on a number of sensory dimensions—sensory differences between rye and bourbon whiskeys as product categories cannot be predicted by mashbill. For producers, consumers, and researchers, this research points to the need for new theories on the origins of flavors in whiskey, as it is now clear that the grain content alone cannot predict sensory qualities.